Communicating shari’ah-compliant brands of tourism in Malaysia - Ahmed, Faruk; Haque, A. K. M. Ahasanul; Abdullah, Kalthom; Razali, Siti Salwani (Malaysian Consumer and Family Economics Association (MACFEA), 2018)
Positive customer-based brand equity entices consumers to buy products or service and the vice versa. Integrated marketing communication can play broader roles in developing conventional and Islamic brand. Fundamentally, Islamic value-based brand image and equity development concept is different from the platform of building image and equity from the contemporary ethical marketing because it is not ethically value-free and free from contemporary ethical value. Islamic value has been added to the contemporary brand image and brand equity concepts and theories as Muslim respondents are questioned on factor statements mixed with conventional and shari’ah-compliant views. From the study, it is revealed that consumer-based brand equity for the shari’ah-compliant tourism of Malaysia was strongly influenced by modern channel based marketing communication through a sequence of two meditators: Islamic country image and shari’ah-compliant tourism brand image, and side by side through the single mediator, shari’ah-compliant tourism brand image; but conventional channel based marketing communication could not produce any significant effects on shari’ah-compliant tourism brand image, Islamic country image, and even on shari’ah-compliant tourism brand equity. Finally, a few effective implications have been identified for building strong customer-based brand equity in terms of advancing shari’ah-compliant tourism of Malaysia, and future research directions are also indicated for the shari’ah-compliant tourism in the Islamic countries according to the scopes of brand equity theory.